A study on marine accidents with particular reference to express passenger boats in Sarawak - Shaari, Mohd Idrus (2001)
A study was conducted in Sarawak with the purpose of (1) analyzing the accident records, reasons and accident patterns, (2) to survey and determine the safety factors of express passenger boats from the point of view of marine department personnel, public and boat passengers and (3) identifying the most common factors causing accidents on express passengers boats. Record show that there are 60 registered vessels and 1,428 boats licensed in Sarawak, of which 688 of them are passenger boats actively operating daily. The types of marine accidents were usually collision, sinking, stranding, capsize, fire, explosion and others. For the period of 1996 to 2000 a total number of 318 marine accidents were recorded by Marine Department Sarawak, with the accidents averaging five to six cases per month. The result of questionnaire distributed to three groups of people namely Marine Department personnel, members of the public, and boat passengers, show that the influencing factors in descending order are: enforcement, human behavior, environments and equipments. They influence accidents on express passenger boats. On the other hand, seagoing express passenger boats show a different order of influencing factors as follows human, environments, enforcement and equipments. The study shows that possibility of marine accidents occurring in the river or sea on express passenger boats are greatly influence by human and enforcement factors. The top four safety issues highlighted in the study ate the serious problem of the Masters attitudes, their skill or competence, unchecked practice of carrying excess passengers and excess cargo. It is strongly believed that there is an urgent need to focus on training and developing safety culture on express passenger boat industry in Sarawak. Therefore proper training and education for express boats operators, particularly to upgrade their skill and competence. An urgent need as well is to educate the public on basic safety precaution when using water transport. Such education will certainly results in more positive attitude towards safety culture. In addition, users will be able to submit constructive suggestions on how to improve safety measures to the authority concerned for improvement.